2011
DOI: 10.1016/j.pmrj.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Early Mobilization in Critically Ill Patients: Patients' Mobilization Level Depends on Health Care Provider's Profession

Abstract: This study showed that physical therapists mobilize their critically ill patients to higher levels compared with nurses. Nurse and physical therapists identify different barriers for mobilization. Routine involvement of physical therapists in directing mobilization treatment may promote early mobilization of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 32 publications
5
88
2
7
Order By: Relevance
“…This study found that physical therapist mobilized their critically ill patient to higher level compare to nurses, i.e., walking with ventilator [32]. However, in Malaysia, most of the ICU did not have its own physical therapist.…”
Section: Background and Literature Reviewmentioning
confidence: 77%
“…This study found that physical therapist mobilized their critically ill patient to higher level compare to nurses, i.e., walking with ventilator [32]. However, in Malaysia, most of the ICU did not have its own physical therapist.…”
Section: Background and Literature Reviewmentioning
confidence: 77%
“…The degree of mobilization a patient receives is dependent upon the type of health care professional responsible for facilitating physical therapy [78]. Physical therapists are able to achieve a higher level of mobilization compared with nurses on an optimal mobilization scale of 0 to 4 (level 2.3 ± 1.2 vs level 1.2 ± 1.2, P b .0001) and have a greater number of patients achieve standing and ambulating (38% vs 13%, P b .05) [78]. The difference between how physical therapists and nurses perceive barriers for advancing mobilization may explain the different patient outcomes.…”
Section: Personnel Resources Attitudes and Perceptionsmentioning
confidence: 99%
“…Therefore, if a patient falls outside of the list in one or a few areas, he or she is excluded from physical therapy at that time. However, Garzon-Serrano et al 19 state that these strict barriers might hurt patients by not allowing them to start therapy at an earlier stage in their hospital stay. These authors advocate for allowing the patients to participate in therapy under the care of a health-care provider who can observe and maintain blood pressure, heart rate, and oxygen saturations within reasonable limits.…”
Section: Early Mobility Entails Patient Riskmentioning
confidence: 99%
“…In 2011, Garzon-Serrano et al 19 identified some important barriers to physical therapy in the ICU. The most commonly identified barriers were continuous renal replacement therapy, hemodynamic instability, and neurologic impairment.…”
Section: Other Logistical Challengesmentioning
confidence: 99%